Breast conserving treatment for breast cancer: dosimetric comparison of different non-invasive techniques for additional boost delivery - Van Parijs, Hilde (BioMed Central, 2014)
BACKGROUND: Today it is unclear which technique for delivery of an additional boost after whole breast radiotherapy for breast conserved patients should be state of the art. We present a dosimetric comparison of different non-invasive treatment techniques for additional boost delivery. METHODS: For 10 different tumor bed localizations, 7 different non-invasive treatment plans were made. Dosimetric comparison of PTV-coverage and dose to organs at risk was performed. RESULTS: The Vero system achieved an excellent PTV-coverage and at the same time could minimize the dose to the organs at risk with an average near-maximum-dose (D2) to the heart of 0.9 Gy and the average volume of ipsilateral lung receiving 5 Gy (V5) of 1.5%. The TomoTherapy modalities delivered an average D2 to the heart of 0.9 Gy for the rotational and of 2.3 Gy for the static modality and an average V5 to the ipsilateral lung of 7.3% and 2.9% respectively. A rotational technique offers an adequate conformity at the cost of more low dose spread and a larger build-up area. In most cases a 2-field technique showed acceptable PTV-coverage, but a bad conformity. Electrons often delivered a worse PTV-coverage than photons, with the planning requirements achieved only in 2 patients and with an average D2 to the heart of 2.8 Gy and an average V5 to the ipsilateral lung of 5.8%. CONCLUSIONS: We present advices which can be used as guidelines for the selection of the best individualized treatment.